The Validity of Colloid e-Module Based STEAM Integrated with Socio-scientific Issues - Miftahul Ulum; Sudarmin Sudarmin; Sigit Priatmoko (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
The need for chemistry teaching materials with technological nuances has become a priority learning resource in the current "freedom of learning" era. This study aimed to produce validity of colloid e-module based  STEAM integrated with socio-scientific issues. The method used was research and development (RD) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluations). In this study, the ADDIE stage was only limited to the development stage, namely validity. The validity test was carried out by four raters consisting of two chemistry lecturers and two chemistry teachers. The data obtained were processed using Aiken's V formula. The results of this research are showed that: (1) The validity of colloid e-module in the media aspect obtained the average value of the Aiken' V index is 0.88 with a high category (2) The validity of colloid e-module in the aspect of content obtained the average value of the Aiken 'V index of 0.90 in the high category. It can be concluded that the colloid e-module based on STEAM integrated socio-scientific issue developed is valid. The next stage will be able to be implemented to find out the effectiveness of e-modules and the response of students during chemical learning.Keywords: Validity, Colloid E-Module, STEAM, Socio-scientific IssuesDOI: 10.23960/jppk.v10.i3.2021.12